Nutritional and Bioactive Composition of Exotic and Indigenous Kalimantan Fruits: Case Studies of Ramania, Kapul, and Ihau Fruits - Utoro, Panggulu Ahmad Ramadhani; Witoyo, Jatmiko Eko (JITIPARI, 2024)
Indonesia is renowned for its rich tropical flora diversity, and Kalimantan Island stands out for its exceptional fruit variety. Three fruits, ramania, kapul, and ihau fruits, have drawn particular interest due to their potential health benefits and possible uses in the food and pharmaceutical industries. Nevertheless, these fruits are rarely explored comprehensively. So, this study offers a better understanding of the diverse fruits found in Kalimantan through a comparative analysis of literature data. This literature review aims to provide valuable insights into the nutritional and bioactive properties of these fruits and highlights their potential health benefits. The results from various previous studies exhibited that the exotic and indigenous fruits from Kalimantan, including ramania, kapul, and ihau fruits, are packed with essential nutrients like proteins, fats, carbohydrates, vitamins, and bioactive compounds that act as anti-aging, anti-bacterial, anticancer, antioxidants, and other bioactivities. Moreover, Kalimantan's exotic and indigenous fruits also have great potential as ingredients for functional food or pharmaceutical production. However, further research is necessary to fully explore their potential and innovative applications in various industries.